Covid-19 As Metaphor and the Illusion of Human Significance - Olajide Wale; Deborah Oluwasola (Britain International for Academic Research (BIAR) Publisher, 2022)
Beyond the debate of which is superior and dominant, nature or nurture is the fundamental claim that nature is not only first and supreme, it is ontologically distinct and separate from all existent that draws of it including man. It is free and disinterested. The Covid virus is of nature and with its ravaging effect as it impacts all facets of human life; it throws human significance into reverse and disrepute. The plea is to give nature its due respect not only as source of support for human life but to continue to uphold its proposed superiority against any claim or suggestion of an overriding human significance. This study opines that the lessons of climate change and the doom it portends for mankind should make this too obvious as the entire human race must now urgently and frantically reverse the devastating consequences already at play as a result of the reckless treatments being meted out to the environment, before he is scorched to death and finally erased.